2019
DOI: 10.1007/978-3-030-17462-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Redundancy for Satisfaction-Driven Clause Learning

Abstract: Satisfaction-Driven Clause Learning (SDCL) is a recent SAT solving paradigm that aggressively trims the search space of possible truth assignments. To determine if the SAT solver is currently exploring a dispensable part of the search space, SDCL uses the so-called positive reduct of a formula: The positive reduct is an easily solvable propositional formula that is satisfiable if the current assignment of the solver can be safely pruned from the search space. In this paper, we present two novel variants of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The shrinking was shown to be correct [21], but has not been implemented so far. We observed that the witnesses in the PR proofs produced by SaDiCaL [20] can be substantially compressed using this method. Fig.…”
Section: Linear Propagation Redundancymentioning
confidence: 99%
See 3 more Smart Citations
“…The shrinking was shown to be correct [21], but has not been implemented so far. We observed that the witnesses in the PR proofs produced by SaDiCaL [20] can be substantially compressed using this method. Fig.…”
Section: Linear Propagation Redundancymentioning
confidence: 99%
“…This section compares the verified CakeML LPR proof checker against other verified checkers on two benchmark suites and a RAT microbenchmark. The first suite is a collection of problems with PR proofs generated by the satisfactiondriven clause learning (SDCL) solver SaDiCaL [20], while the second suite consists of unsatisfiable problems from the SAT Race 2019 competition. 6 The RAT microbenchmark consists of proofs for large mutilated chessboards generated by a BDD-based SAT solver [5].…”
Section: Benchmarksmentioning
confidence: 99%
See 2 more Smart Citations
“…DPR allows for short proofs without the need for new variables, thus making it a strong candidate for practical SAT solving. In fact, the solver SaDiCaL [15], which implements the DPR-based satisfaction-driven clause learning (SDCL) paradigm [14], can automatically find short proofs of the pigeon-hole principle, Tseitin formulas over expander graphs [30], and mutilated chessboard problems [25]. All these problems are infamous in the proof-complexity literature for being extremely hard [1,8,9,31], thus causing usual conflict-driven clause learning (CDCL) [24,26] solvers some serious trouble.…”
Section: Introductionmentioning
confidence: 99%